TEACHER MOTIVATION AND JOB SATISFACTION: A STUDY ON TEACHERS IN THREE DISTRICTS IN NORTHERN SRI LANKA - Mangaleswarasharma, R (PEOPLE: International Journal of Social Sciences, 2017)
The study explores the motivation and job satisfaction of teachers with the objectives to study the factors that related to the choice of their job and their job satisfaction. Population of the study involved the teachers in Sri Lanka and the target population of the study consisted of teachers in three districts in Northern Sri Lanka. A sample of one hundred and fifty teachers participated in a workshop was purposively selected for this study. A self-developed questionnaire, built up by reviewing related literature was used for data collection. Quantitative data collected through questionnaire survey was analyzed using simple descriptive statistics including frequencies and percentages. Qualitative data was analyzed by categorizing and coding into emerging themes. Findings from the study revealed that, 79% of the teachers agreed that they selected teaching profession on their own choice. 82% of them involve in teaching with full satisfaction. However 29% of the teachers wanted to go to some other jobs. Further, the results of this study indicated that, teachers selected this profession as they preferred it, it is a permanent job and it has long holidays and less working hours. Among the teachers who involved in teaching with full satisfaction, 45% expressed that they loved it. Based on the findings, the study concluded that, teachers have motivation towards their profession. However, some of them felt that, they are not fully satisfied with their job and wanted to get some other jobs. It is therefore recommended that teachers should be provided with relevant training and professional development opportunities, salary increase and respect and recognition to motivate them and to increase their job satisfaction.